A study on the response of the LR-115 detector exposed inside a diffusion chamber and in unconventional bare mode - Bertin Andrés, Pérez Ancaya (Pontificia Universidad Católica del Perú, 2021)
Several methodologies for radon concentration measurements have been used for monitoring radon in homes and workplaces to minimize health hazards due to indoor radon exposure. One of them is the Nuclear Track Methodology (NTM), commonly used for passive long-term measurements. The LR-115 type II (cellulose nitrate), as an NTM’s detector, is often located inside a diffusion chamber. The set formed by the detector and the chamber hereinafter will be called a monitor. Commercial monitors, e.g., RadOUT , Radosys, NRPB, are routinely used for radon measurements; they are calibrated in Certified and/or Accredited Laboratories. However, many laboratories have developed their own monitors, varying some characteristics as geometric shapes, dimensions, and material properties. They also do not have access to calibrate them in Certified and/or Accredited Laboratories. In the present thesis, we studied the detector response given the characteristics of the diffusion chamber that we use, and to know how these characteristics influence radon measurements. The results of this study can provide a fast-calibration of the detector that can be compared to calibrations in Certified and/or Accredited Laboratories. This study is based on Monte Carlo methods that imitate the experimental procedure commonly-used in estimating the calibration factor. This calibration method is more accesible than calibrations performed in Certified and/or Accredited Laboratories due to its low cost, feasibility and applicability. For these purposes, a monitor (LR-115 + a non-commercial diffusion chamber made of polypropylene -usually used as cosmetic pot-) was used in this research. LR-115 detector response in this set-up is reported by taking into account the geometric shape, dimensions and material (conductive or non-conductive) of the chamber, the transmission factor (the ratio of final steady state concentration of radon or thoron at the entrance of the chamber to the concentration of radon or thoron just inside this entrance), radon exposure level, and etching and reading process. Regarding the level of radon exposure, it was possible to correct the track overlap effect for high exposure levels, as can occur in radon measurements in soil pores, by applying a mathematical model. Mainly, these researches show that a non-commercial monitor can work as well as commercial ones. Besides, using an LR-115 in bare mode exposed by unconventional exposition results in concentric ring-shaped tracks, caused by UV natural radiation. The repeatability and reproducibility of the observed phenomenon were experimentally demonstrated. We also studied the ability of the LR-115 detector to register alpha particles from nuclear (n,α) reactions, or radon/thoron progeny. This study is also based on Monte Carlo methods and can provide an estimation of the efficiency of the detector to neutron or radon/thoron progeny.
Keywords: Detectores; Partículas alfa; Radón; https://purl.org/pe-repo/ocde/ford#1.03.00